Effect of Cellulose Acetate Beads on Interleukin‐23 Release. Issue 4 (August 2016) - Nishise, Shoichi; Abe, Yasuhiko; Nomura, Eiki; Sato, Takeshi; Sasaki, Yu; Iwano, Daisuke; Yoshizawa, Kazuya; Yagi, Makoto; Sakuta, Kazuhiro; Ueno, Yoshiyuki
Abstract: Interleukin (IL)‐23, which is released by activated monocytes and neutrophils, promotes production of high levels of IL‐17 by T‐helper 17 cells. Cellulose acetate (CA) beads are used as carriers for granulocyte and monocyte (GM) adsorptive apheresis using Adacolumn. Contact between blood and CA beads induces cytokine release; however, their inflammatory effects on IL‐23 release are unclear. We aimed to clarify the effect of CA beads on IL‐23 release in vitro. We incubated peripheral blood with and without CA beads and measured IL‐23. Compared to blood samples incubated without CA beads, blood samples incubated with CA beads had significantly decreased amounts of IL‐23. In conclusion, CA beads inhibited IL‐23 release from adsorbed GMs. The biological effects of this decrease in IL‐23 release during GM adsorption to CA beads need further clarification.